Leveraging the Medicines for Malaria Venture malaria and pathogen boxes to discover chemical inhibitors of East Coast fever. (April 2019) - Nyagwange, James; Awino, Elias; Tijhaar, Edwin; Svitek, Nicholas; Pelle, Roger; Nene, Vishvanath
Abstract: Chemotherapy of East Coast fever, a lymphoproliferative cancer-like disease of cattle causing significant economic losses in Africa, is largely dependent on the use of buparvaquone, a drug that was developed in the late 1980's. The disease is caused by the tick-borne protozoan pathogen Theileria parva . Buparvaquone can be used prophylactically and it is also active against tropical theileriosis, caused by the related parasite Theileria annulata . Recently, drug resistance was reported in T. annulata, and could occur in T. parva . Using a 3 H-thymidine incorporation assay we screened 796 open source compounds from the Medicines for Malaria Venture (MMV) to discover novel chemicals with potential inhibitory activity to T. parva . We identified nine malaria box compounds and eight pathogen box compounds that inhibited the proliferation of F100TpM, a T. parva infected lymphocyte cell line. However, only two compounds, MMV008212 and MMV688372 represent promising leads with IC50 values of 0.78 and 0.61 μM, respectively, and CC50 values > 5 μM. The remaining compounds exhibited a high degree of toxicity (CC50 values < 1.09 μM) on the proliferation of bovine peripheral blood mononuclear cells stimulated with concanavalin A. We also tested the anti-cancer drug, dasatinib, used in the chemotherapy of some leukemias. Dasatinib was as active and safe as buparvaquone in vitro, with an IC50 of 5 and 4.2 nM, respectively, and CC50 > 10 μM. Our preliminary data suggest that it may be possible to repurpose compounds from the cancer field as well as MMV as novel anti- T. parva molecules. Graphical abstract: Image 1 Highlights: 17 of 796 MMV compounds inhibited proliferation of T parva infected lymphocytes. 15 of the 17 hit compounds also inhibited proliferation of control cells. MMV008212 and MMV688372 represent promising leads, therapeutic index >8. Dasatinib was as active and safe as buparvaquone in vitro, therapeutic index >2000.